Correction of regulatory molecules expression at the inflammation stage using photobiomodulation therapy in chronic wound modeling - М.V. Kumechko; N.М. Babenko; S.B. Pavlov; О.B. Litvinova; І.І. Torianyk; О.І. Babaieva (Journal of V. N. Karazin Kharkiv National University: Series Medicine)
Background. The search for effective treatments for chronic wounds continues. Photobiomodulation is a therapeutic approach that promotes cell differentiation, proliferation, and accelerated wound healing. The production of cytokines and growth factors determines the wound healing process, and their dysregulation can lead to wound chronicity. Therefore, by adjusting the levels of cytokines and growth factors, it is possible to influence the wound healing process.